Duration and intensity of occupational lifting and risk of long-term sickness absence: Prospective cohort study with register follow-up among 45 000 workers - Bláfoss, Rúni; Skovlund, Sebastian Venge; Skals, Sebastian; Sundstrup, Emil; López-Bueno, Rubén; Calatayud, Joaquín; Andersen, Lars Louis (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVE ': 'This study aimed to investigate the prospective association of lifting duration and lifting load with the risk of long-term sickness absence (LTSA). ' ' METHODS ': 'We followed manual workers with occupational lifting (N=45 346) from the Work Environment and Health in Denmark Study (2012–2018) for two years in a high-quality national register on social transfer payments (DREAM). Cox regressions with model-assisted weights were employed to estimate the risk of LTSA from lifting duration and loads. ' ' RESULTS ': 'During follow-up, 9.6% of the workers had an episode of LTSA. Compared to workers with seldom lifting (reference), workers lifting ½ and ¾ of the workday had increased risk of LTSA [hazard ratios (HR) of 1.36 [95% confidence interval (CI) 1.20–1.56] and 1.22 (95% CI 1.07–1.39)], respectively. Lifting load showed a positive exposure–response association with LTSA (trend test, P<0.01), with HR for lifting 5–15, 16–29, and ≥30 kg at 1.11 (95% CI 1.02–1.22), 1.17 (95% CI 1.03–1.34), and 1.29 (95% CI 1.11–1.50), respectively. Age-stratified analyses showed increased risk of LTSA among workers ≥50 years with a high proportion of work-related lifting compared to their younger counterparts. ' ' CONCLUSIONS ': 'Occupational lifting for ½ the workday increased the risk of LTSA, while higher occupational lifting load exacerbated this risk in an exposure–response manner. The study underscores the importance of reducing both lifting duration and loads for prevention of LTSA at the workplace, especially among older workers.
Keywords: absenteeism; aging; cohort study; long-term sickness absence; musculoskeletal disease; occupational exposure; occupational lifting; physical workload; public health; sickness absence; socioeconomic factor